Hypothyroxinemia induced by maternal mild iodine deficiency impairs hippocampal myelinated growth in lactational rats. Issue 11 (18th April 2014) - Wei, Wei; Wang, Yi; Dong, Jing; Wang, Yuan; Min, Hui; Song, Binbin; Shan, Zhongyan; Teng, Weiping; Xi, Qi; Chen, Jie
ABSTRACT Hypothyroxinemia induced by maternal mild iodine deficiency causes neurological deficits and impairments of brain function in offspring. Hypothyroxinemia is prevalent in developing and developed countries alike. However, the mechanism underlying these deficits remains less well known. Given that the myelin plays an important role in learning and memory function, we hypothesize that hippocampal myelinated growth may be impaired in rat offspring exposed to hypothyroxinemia induced by maternal mild iodine deficiency. To test this hypothesis, the female Wistar rats were used and four experimental groups were prepared: (1) control; (2) maternal mild iodine deficiency diet inducing hypothyroxinemia; (3) hypothyroidism induced by maternal severe iodine deficiency diet; (4) hypothyroidism induced by maternal methimazole water. The rats were fed the diet from 3 months before pregnancy to the end of lactation. Our results showed that the physiological changes occuring in the hippocampal myelin were altered in the mild iodine deficiency group as indicated by the results of immunofluorescence of myelin basic proteins on postnatal day 14 and postnatal day 21. Moreover, hypothyroxinemia reduced the expressions of oligodendrocyte lineage transcription factor 2 and myelin‐related proteins in the treatments on postnatal day 14 and postnatal day 21. Our data suggested that hypothyroxinemia induced by maternal mild iodine deficiency may impair myelinated growth of the offspring. © 2014 Wiley Periodicals, Inc. Environ Toxicol 30: 1264–1274, 2015.